The Dance of Spirit in AEPL - Susan Schiller (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Co-editor of The Spiritual Side of Writing examines AEPL’s role in the global pedagogical movement it has participated in for over 20 years.